Democracy promotion by functional cooperation : the European Union and its neighbourhood /: the European Union and its neighbourhood. ([2015]) - Freyburg, Tina; Lavenex, Sandra; Schimmelfennig, Frank, 1963-; Skripka, T. V (Tatʹi︠a︡na Vladimirovna); Wetzel, Anne, 1979-
No abstract available